Reproductive disorders and obstetric complications in gynecological diseases - A L Unanian; I S Sidorova; A D Nikonets; L N Aminova; V A Alimov; A V Shchukina; Yu V Chushkov; D V Baburin (IP Berlin A.V., 2018)
This publication examines the existing risks of obstetric complications and other reproductive disorders in women with gynecological diseases. The paper also discusses the issues of the pre-school training of women with gynecological diseases, with special emphasis on the use of dipyridamole, due to its pleiotropic action.